Qur’anic Texts and Noble Narrations and the Identification of the Reality of Imamate According to Divine Will - كاظم زينب محمد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Imamate is one of the most important fundamental issues in the life of the nation. Some Islamic sects believe that Islamic law does not interfere in determining its validity. Their evidence for that is the Almighty’s saying: “And their rule is by consultation among themselves” (13:1). They believe that the Prophet (peace and blessings of Allah be upon him and his family) neglected to define that so as not to cause hardship to Muslims by restricting themselves to choosing a ruler to suit and fit the development of time and the changing lifestyles according to successive eras. Moreover, he did not specify the method of choosing him after him, but rather explained to Muslims the general rules that the ruler must take into account in his conduct and clarified the ideals and supreme values that both the ruler and the ruled should adhere to. They used the sayings and actions of the Companions as evidence in legislating laws and developing theories on these issues In their view, Imamate is one of the branches of religion and not one of its principles, and this is the origin of the disagreement on this issue. Hence, my research entitled “The Qur’anic Texts and the Noble Narrations and the Diagnosis of the Evidence of Imamate According to the Will of Heaven” came to deal with the Qur’an and the narration that diagnosed the Evidence of Imamate by presenting those noble texts and analyzing their contents. Thus, the problem presented in this position can be resolved by diverting the meaning of “Imamate” from the infallible Imams (peace be upon them).